Frozen Meat Against COVID-19 Misinformation: An Analysis of Steak-Umm and Positive Expectancy Violations. (January 2021) - Bogomoletc, Ekaterina; Lee, Nicole M.
COVID-19 has forced many businesses to adjust their communication strategies to fit a new reality. One surprising example of this strategy adjustment came from the company Steak-umm, maker of frozen sliced beef. Instead of finding new ways to promote its products, the company shifted its focus to the public's urgent needs, breaking down possible approaches to navigating information flow during the pandemic. This resulted in overwhelming praise on social and news media, including almost 60, 000 new Twitter followers within a week. Drawing on expectancy violation theory, this case study examines Steak-umm's strategy, the content of social media responses, and why the approach was successful.